Trade Openness and Environmental Pressure on Agribusiness Sustainability in ASEAN-5 Emerging Economies - Annisa Rahayu; Taufiq Marwa; Imam Asngari (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines how environmental pressure, trade openness and agricultural employment relate to agribusiness sustainability in the ASEAN-5 over 2002–2024. A balanced panel of 115 country-year observations is estimated using Fixed Effects, FE-EGLS, FMOLS as the main model, and DOLS as a robustness check. Trade openness is negative and agricultural employment positively associated with agribusiness sustainability in all four specifications. Agricultural carbon emissions carry a negative coefficient throughout but lose significance under DOLS and are therefore sensitive to the estimator. The findings suggest that excessive trade liberalisation may weaken domestic agribusiness resilience, while agricultural labour remains important for food security. Keywords: Agribusiness Sustainability; Trade Openness; Agricultural Emissions; ASEAN-5; Panel Cointegration; FMOLS